Hydrolethalus Syndrome: A Case of a Rare Congenital Disorder - Valerica Belengeanu; Diana Marian; Horia Ademir Stana; Carolina Cojocariu; Cristina Popescu; Ioana Elena Lile (Diagnostics)
This is a fatal case of multiple complicated congenital anomalies displaying several symptoms consistent with hydrolethalus syndrome. The newborn’s phenotype is characterized by a combination of serious anatomical abnormalities such as open-book cerebral hemispheres, defective lobulation of the lungs (one lobe on the left, two on the right), a smaller right kidney, a smooth cerebral surface, and a specific keyhole-shaped defect in the skull base, primarily associated with hydrocephalus.